A review of the ESL/EFL learners’ gains from online peer feedback on English writing - Cao, Siyi; Zhou, Siruo; Luo, Yong; Wang, Tao; Zhou, Tongquan; Xu, Yizhong (Frontiers in Psychology, 2022)
Peer feedback is essential in writing English as a Second/Foreign Language (ESL/EFL). Traditionally, offline PF was more widely favored but nowadays online peer feedback (OPF) has become frequent in ESL/EFL learners’ daily writing. This study is undertaken to probe into the gains of using OPF in ESL/EFL writing on the basis of 37 research articles published in core journals from 2012 till 2022. In order to accurately cover the previous researches, we capitalize on three methods to evaluate and analyze the data, i.e., database search, citation search and manual search. Results show that from the perspective of the ESL/EFL learners’ gains, the OPF is basically divided into two categories (cognitive OPF and affective OPF), involving eight aspects in all: face-based strategies, revision-based comments, writing performance, learning environment, reflection/critical thinking/responsibility, writing emotion, motivation, and attitudes; and OPF can be well supported by a set of theories like Process-oriented Writing Theory, Collaborative Learning Theory, Interactionist Theory of L2 Acquisition and Vygotsky’s sociocultural theory. By comparison, the gains from OPF outperform those from offline PF in many dimensions (e.g., face-based strategies), despite some overlaps (e.g., the shift of the role) that were revealed in several investigations. Based on the past studies, we propose some pedagogical implications on OPF from ESL/EFL writing, including accenting the “student-centered” teaching strategy, providing students with OPF on the basis of incremental knowledge, adopting OPF regularly in ESL/EFL writing activities to shape personalities and outlooks and putting OPF into its full play with recourse to abundant internet-based vehicles. This review is desired to provide a guideline for both the peer feedback practice and the upcoming scholarly researches with respect to EFL/ESL writing.